ANALISIS PENDAPATAN UMKM DI SEKITAR UNIVERSITAS TIDAR TAHUN 2018 (Studi khasus sebelum dan sesudah Universitas Tidar menjadi negeri di Tuguran kelurahan Potrobangsan Kecamatan Magelang Utara ) - Saktya Chandra Kusuma; Whinarko Juliprijanto; Gentur Jalunggono (DINAMIC : Directory Journal of Economic, 2019)
This type of research is quantitative research, which is a study that aims to obtain proof of a hypothesis. Data collection is done by questionnaire and direct observation. The sample used as many as 23 Small and Medium Micro Business actors with simple random sampling technique means that it is said to be simple because the taking of sample members from the population is done randomly regardless of the strata that exist in that population. The data analysis technique used to answer the first problem statement is the two different Average Test. The two different test averages used in this study are two different test averages for small samples and the analysis was carried out using data tabulation by percentage of respondents' answers regarding each aspect of indicators of increasing MSME income in the community.Based on the results of the calculation of two different tests on average, the writer did by using the value of the degree of truth (α) = 0.05% and using two-sided testing to produce a t value of -0.11. The t value fulfills the H0 criterion accepted if - 1.68 ≤ t ≤ 1.68. What means that the establishment of Tidar University contributes to the increase in income of Micro, Small and Medium Enterprises. Keywords: Revenue and  MSMEs